Feeding patterns in a fish community of Baia da Onça, a floodplain lake of the Aquidauana River, Pantanal, Brazil - Catella, A. C.; Petrere, M. [UNESP] (Wiley, 1996)
The stomach contents of 24 species of fish and unidentified species from four genera in a floodplain lake of the Pantanal were studied. Fish were collected during the dry season when the lake was isolated from the main river. A community food ingestion index (feeding index weighted by consumer biomass, FIWCB, where 0 < FIWCB < 1) was calculated to quantify feeding patterns. Detritus and algae ingested by Curimatidae were responsible for 46.5% of the FIWCB, while that for algae ingested by Loricariidae (armoured catfish) accounted for 13.2%. The importance of detritus in fish diets is discussed as a strategy for shortening food chains, thereby increasing community efficiency, and as a consequence, fish biomass. It was learnt that the main route of energy flow in this perennial lake was through the detritus chain. The floodplain lakes function as a dry season feeding ground for small-sized species of fish, which are potential prey for the more highly valued larger species of fish.
Keywords: Feeding index; Fish community feeding; Food chain; Pantanal; Stomach contents